Effects of genomic location on ectopic integration and gene expression of a reporter gene cassette in Sulfolobus acidocaldarius - Xu, Yifei; Peeters, Andries Ivo; Bervoets, Indra; De Mey, Marjan; Baes, Rani; Peeters, Eveline (Frontiers in Microbiology, 2025)
In eukaryotes and bacteria, it is well-established that the genomic location of ectopic gene integration influences the expression level due to replication-associated gene dosage effects as well as effects mediated by chromatin organization. In contrast, in archaea, the impact of genomic location on gene expression remained unexplored. Here, we investigated this impact in the model archaeon Sulfolobus acidocaldarius, a crenarchaeal species that has a chromatin architecture with mixed eukaryotic-like and bacterial-like features. We aimed to integrate a standardized β-galactosidase (lacS) reporter cassette into diverse loci in the genome of S. acidocaldarius SK-1 for a comparative analysis. Nine integration mutant strains were successfully obtained, for which qRT-PCR analysis and lacS reporter gene assays revealed significant variation in transcriptional and translational expression of the reporter, respectively, demonstrating that genomic location strongly influences gene expression in S. acidocaldarius. However, variability in transcription levels and its regulation was shown to be primarily driven by transcriptional activity of neighboring genes, due to the high coding density in the S. acidocaldarius genome as well as a lack of insulator elements. In conclusion, this study not only provides insights into genome context effects, but also provides inspiration for the future design of genomic knock-in constructions in S. acidocaldarius.